Genetic variation in Hydrangea macrophylla (Thunb.) Ser. in Russia based on simple sequence repeat markers (Bangladesh Journal of Botany, 2018)
Genetic diversity and genetic relationships among 39 accessions of Hydrangea macrophylla (Thunb.) Ser. were analyzed using 38 previously developed simple sequence repeat markers (SSRs). A total of 38 polymorphic primers representing 166 bands with an average of 4.53 polymorphic bands per primer were selected. The number of alleles detected per locus ranged from two to eight with a total of 163 alleles amplified. The size of the amplified fragments ranged from 70 to180 base pairs. The effective multiallelic markers with high level of heterozygosity (more than 0.7) and effective number of alleles (more than 3.5) were identified. In this study nine SSR markers showed clear polymorphisms. The dendrogram grouped all hybrids in three major clusters, and two of these clusters included only mophead cultivars. The lacecap cultivars clustered more closely to each other. The results of this research could be used in breeding programs of H. macrophylla.